Hearing science fundamentals - Lass, Norman J.; Donai, Jeremy J. (Jeremy James) (San Diego, CA : Plural Publishing, Inc., 2023)
'Hearing Science Fundamentals, Second Edition maintains the straightforward style of the previous edition, introducing the basic concepts in hearing science in an easy-to-understand format. With a wide variety of student-friendly features and instructor resources, this comprehensive textbook facilitates the absorption of technical material by both undergraduate and graduate students'--
Basic Acoustics -- Review of Speech Acoustics / Helen A. Boyd-Pratt and Jeremy J. Donai -- Digital Signal Processing -- Anatomy and Physiology of the Conductive Auditory Mechanism -- Anatomy and Physiology of the Sensory Auditory Mechanism -- Anatomy and Physiology of the Central Auditory Mechanism -- Normal Hearing -- Binaural Processing -- Masking -- Temporal Processing -- Loudness and Pitch -- Differential Sensitivity -- Auditory Perception and Hearing Impairment -- Pathologies of the Conductive Auditory Mechanism -- Pathologies of the Sensory Auditory Mechanism -- Pathologies of the Central Auditory Mechanism.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on November 16, 2021).
WorldCat record variable field(s) change: 650
Keywords: Hearing -- Physiology; Ear -- Physiology; Auditory perception -- Physiology; Psychoacoustics; Hearing -- physiology; Ear -- physiology; Ear -- anatomy & histology; Auditory Perception -- physiology; Psychoacoustics; Oreille -- Physiologie; Perception auditive -- Physiologie; Psychoacoustique; Ear -- Physiology; Electronic books